Kepala sekolah sebagai Power Peningkatan Loyalitas Guru di SMP Negeri 1 Mojoagung Jombang - Sunardi Sunardi; Hamdan Ibnu Sihab (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2023)
Loyalty is an extremely important quality in a leader, and its presence guarantees the growth of a dedicated following. A competent instructor will carry out the required actions. Therefore, it is necessary to increase teacher loyalty to their jobs, as teachers play a crucial role in the educational process. Teachers who are not committed to their institutions typically display low levels of motivation and professionalism in the classroom. The purpose of this study is to de-emphasize teacher loyalty and instead learn how the school's administration plans to increase teacher loyalty at SMP Negeri 1 Mojoagung Jombang. This type of study is a descriptive quantitative study. Instead, observation, interviews, and paperwork are used as data collection methods. Meanwhile, common data analysis techniques include data reduction, data presentation, and data verification. However, the study's findings pertain to teachers' loyalty at SMP Negeri 1 Mojoagung Jombang, and they are as follows: strict adherence to established rules and regulations, acceptance of responsibility for the responsibilities placed on him as a teacher and the tasks assigned to him, and a commitment to communicating truthfully and in accordance with Islamic principles. In contrast, the school's administration can boost teacher loyalty by measures such as increased surveillance, providing teachers with feedback and coaching opportunities, conducting regular classroom observations, reminding teachers of their professional obligations, reminding teachers that the school is their own, providing uswatun khasanah.